VERBALPHRASE MIT PRÄPOSITION AND PRÄPOSITIONALPHRASE IN GERMAN - Amalina Rachmi Fatina (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
This paper is aimed to examine the construction elements of Verbalphrase mit Präposition and Präpositionalphrase in German and the matters that influence it. The result of this paper indicates that Verpbalphrase mit Präposition is followed by prepositions and it is also influenced by subjects and cases. Präpositionalphrase can be formed from prepositions are followed by noun phrases and cases of Akkusativ, Dativ, and Genitiv. On the other hand, there are types of prepositions can be influenced by cases of Akkusativ and Dativ. The preposition is called Wechselpräpositionen. Verpbalphrase mit Präposition and Präpositionalphrase can be found in one sentence, so that, sentence can be formed from two types of phrases. In the sentence is also found that the prepositions of the two phrases influenced by two different cases, namely the case of Akkusativ and Dativ.Keywords: German, phrase, Verbalphrase mit Präposition, Präpositionalphrase, phrase verb phrase, preposition phrase, syntax